Solve for u
u=-2
u=0
Share
Copied to clipboard
u\left(6u+12\right)=0
Factor out u.
u=0 u=-2
To find equation solutions, solve u=0 and 6u+12=0.
6u^{2}+12u=0
All equations of the form ax^{2}+bx+c=0 can be solved using the quadratic formula: \frac{-b±\sqrt{b^{2}-4ac}}{2a}. The quadratic formula gives two solutions, one when ± is addition and one when it is subtraction.
u=\frac{-12±\sqrt{12^{2}}}{2\times 6}
This equation is in standard form: ax^{2}+bx+c=0. Substitute 6 for a, 12 for b, and 0 for c in the quadratic formula, \frac{-b±\sqrt{b^{2}-4ac}}{2a}.
u=\frac{-12±12}{2\times 6}
Take the square root of 12^{2}.
u=\frac{-12±12}{12}
Multiply 2 times 6.
u=\frac{0}{12}
Now solve the equation u=\frac{-12±12}{12} when ± is plus. Add -12 to 12.
u=0
Divide 0 by 12.
u=-\frac{24}{12}
Now solve the equation u=\frac{-12±12}{12} when ± is minus. Subtract 12 from -12.
u=-2
Divide -24 by 12.
u=0 u=-2
The equation is now solved.
6u^{2}+12u=0
Quadratic equations such as this one can be solved by completing the square. In order to complete the square, the equation must first be in the form x^{2}+bx=c.
\frac{6u^{2}+12u}{6}=\frac{0}{6}
Divide both sides by 6.
u^{2}+\frac{12}{6}u=\frac{0}{6}
Dividing by 6 undoes the multiplication by 6.
u^{2}+2u=\frac{0}{6}
Divide 12 by 6.
u^{2}+2u=0
Divide 0 by 6.
u^{2}+2u+1^{2}=1^{2}
Divide 2, the coefficient of the x term, by 2 to get 1. Then add the square of 1 to both sides of the equation. This step makes the left hand side of the equation a perfect square.
u^{2}+2u+1=1
Square 1.
\left(u+1\right)^{2}=1
Factor u^{2}+2u+1. In general, when x^{2}+bx+c is a perfect square, it can always be factored as \left(x+\frac{b}{2}\right)^{2}.
\sqrt{\left(u+1\right)^{2}}=\sqrt{1}
Take the square root of both sides of the equation.
u+1=1 u+1=-1
Simplify.
u=0 u=-2
Subtract 1 from both sides of the equation.
Examples
Quadratic equation
{ x } ^ { 2 } - 4 x - 5 = 0
Trigonometry
4 \sin \theta \cos \theta = 2 \sin \theta
Linear equation
y = 3x + 4
Arithmetic
699 * 533
Matrix
\left[ \begin{array} { l l } { 2 } & { 3 } \\ { 5 } & { 4 } \end{array} \right] \left[ \begin{array} { l l l } { 2 } & { 0 } & { 3 } \\ { -1 } & { 1 } & { 5 } \end{array} \right]
Simultaneous equation
\left. \begin{cases} { 8x+2y = 46 } \\ { 7x+3y = 47 } \end{cases} \right.
Differentiation
\frac { d } { d x } \frac { ( 3 x ^ { 2 } - 2 ) } { ( x - 5 ) }
Integration
\int _ { 0 } ^ { 1 } x e ^ { - x ^ { 2 } } d x
Limits
\lim _{x \rightarrow-3} \frac{x^{2}-9}{x^{2}+2 x-3}